(3EOGQI GdeTQhYGJs - (3eMeO YHO(B, (3CHh SeQIs ((3YeGf(B:s (3OGQ GdQGjI ddfTQ hGdJhRjY(B,s, 2010)
(3eONd Gdi GdGOGQI, JhUjja GdeTQhYGJ h OQGSGJ GdLOhi ddeTQhYGJ, GYGOI JfXje h gjcdI GdeTQhYGJ, EOGQI GdeTQhYGJ GdJLGQjI GdUZjQI h CNjQG EOGQI GdeTQhYGJ GdUZjQIs
(3HHdjhZQGajG(B: (3U(B.193-194s
Keywords: (3EOGQI GdCYeGds; (3GdeTQhYGJ(B- (3JfXje hEOGQIs; (3OQGSI GdLOhis